Assessment of quality of life in patients undergoing periodontal flap surgery using the questionnaire for patient-based outcomes following periodontal therapy - Birina Deka; Prasad Nadig; Monali Shah; Tanvi Tilokani; Hardi Gandhi (SRM Journal of Research in Dental Sciences)
Background: After periodontal therapy, metrics such as pocket probing depth and clinical attachment level are typically measured, but patient-centered outcomes are often overlooked. It is important to enhance the evaluation of flap surgery outcomes with a questionnaire that gauges the quality of life in patients, postprocedure. The questionnaire for patient-based outcomes following periodontal therapy (QPBOPT) includes 14 items that investigate the potential observations and expectations of patients following periodontal treatment. Materials and Methods: A cross-sectional observational study was conducted with 51 patients who had received periodontal flap surgery. The QPBOPT was administered 3 months after the treatment, and the collected data were then subjected to statistical analysis. Results: All patients (100%) reported a decrease in bleeding gums, and 96% noticed an improvement in bad breath following surgery. Nevertheless, 68.6% of patients were discontented with the positioning of their gums, whereas 76.5% continued to experience sensitivity after the procedure. Conclusion: Significant improvements were seen in most dimensions except for the position of gums and sensitivity from the patient’s perspective. Hence, there is a need to address both the esthetic expectations of the patient and the hypersensitivity following flap surgery.